Acute and Sub-Acute Toxicity Studies and Pharmacodynamic Studies of Standardized Extract of Trachyspermum ammi (L.) Sprague (Fruits) Against Chemically Induced Inflammation in Rats - Saraswat, Nikita; Sachan, Neetu; Chandra, Phool (Current Drug Discovery Technologies, 2021)
Introduction: Nowadays, researchers have been attempting to use herbal products as medicines which have proven to cause lesser side effects. The fruit part of Trachyspermum ammi (L.) - Ajwain has been an integral part of the Indian medicine system with much importance in Ayurveda and Unani medicine system and is prescribed by Vaidya gurus and Hakim in raw form or as a major constituent in the powdered formulations. Objective: This research aimed to evaluate acute and sub-acute toxicity of standardized T. ammi fruit and its anti-inflammatory property using experimental models. Methods: The extract of herbs was spectroscopically analyzed for the estimation of the number of bioactive compounds. Then acute and sub-acute toxicity analysis of the herbal extract was performed to ensure the toxic effects, if any. Biochemical parameters like ALT, AST, ALP, etc. and histopathological analysis were determined to study the toxicity of the extract. Then, the anti-inflammatory activity of the T. ammi fruit extract employing Carrageenan and formalin-induced edema model in rats was studied. Results: Ajwain seeds have a pungent smell and a characteristic odor. The powder microscopy clearly showed endosperm, unicellular warty trichomes, striated cuticle in surface view, vittae, endodermis, and vascular strand. Phytochemical tests reported the presence of carbohydrates, alkaloids, tannins, etc. and characteristic peaks in UV, Mass, NMR, FTIR and HPLC were observed for the extract. Acute and sub-acute toxicity studies did not report any toxicity, and significant anti-inflammatory action was recorded. Conclusion: The spectroscopic and pharmacognostic analysis has shown the strong presence of flavonoids, mineral matter, protein, phenols, saponins, carbohydrates, volatile oils, fiber, glycosides and fat. Spectroscopic study interpretations have shown the presence of compounds like thymol, para-cymene, γ-terpinene, α- and β-pinene, carvone, limonene, saponins,, β-phellandrene, βfenchyl alcohol, α-thujene, β-phellendrene, α-thujene, etc. No signs of toxicity were recorded in acute and sub-acute toxicity studies assessing the relative weight and histopathological analysis. Significant anti-inflammatory potential of T. ammi fruit extract was found and LD50 was found to be beyond 3000 mg/kg. The results of this study could be useful; in setting the quality parameters for further identification of the crude herb and preparation of the monograph.
Keywords: Trachyspermum ammi (L.)